Wheat blast : a threat to wheat cultivation - R, Madhubala; Bhagyalahari, B; Sujeetha, J Alice R P (Indian Farming, 2018)
The wheat crop in northern region of India could be threatened by a fearsome and devastating disease called wheat blast which caused an outbreak in the neighboring country Bangladesh. This disease was detected for the first time in Asia with reports of a severe outbreak in 8 districts of Bangladesh during 2016. The disease is caused by a fungal pathogen Magnaporthe oryzae Triticum pathotype (MoT) and the most common symptom observed in the field is head infection. The pathogen spreads by seed and air and it survives on crop residues.